A comparative analysis of microstructural features, tensile properties and wettability of hypoperitectic and peritectic Sn-Sb solder alloys - Dias, Marcelino (2018)
Sn-Sb alloys are among the current alternatives for the development of alloys for high-temperature lead-free solders. The Sn-Sb alloys having 5.5 wt.% Sb or less are known to have good mechanical properties, and despite the quite low liquidus temperature have been considered adequate in the development of solder joints. The increase in the Sb content up to the limit of solubility in Sn at about 10 wt.% is supposed to be detrimental to the mechanical properties due to the extensive formation of an intermetallic compound. Investigations on the interrelation of microstructure of this alloy and the corresponding mechanical properties are fundamental to an appropriate evaluation of its application in solder joints. The present investigation analyses the relationship between microstructural features of the peritectic Sn-10 wt.% Sb alloy, solidified under a wide range of cooling rates, and the resulting mechanical properties. A cellular β-Sn matrix, typified by cellular spacings that decrease with the increase in the solidification cooling rate, and Sn3Sb2 particles are shown to characterize the alloy microstructure. The ultimate tensile strength is higher as compared with the corresponding values of the hypoperitectic Sn-5.5 wt.% Sb solder alloy, however the elongation is shown to decrease. A comparison with Bi-Ag alloys, considered good high temperature solders alternatives, has shown that the tensile properties of the Sn-10 wt.% Sb alloy, including elongation, are significantly higher. Wettability tests have been carried out and the experimental results, according to reports from the literature, are associated with good wettability